Cortical and subcortical morphometric changes and their relation to cognitive impairment in isolated REM sleep behavior disorder - Mala, Christiane; Havlík, Filip; Mana, Josef; Nepožitek, Jiří; Dostálová, Simona; Růžička, Evžen; Šonka, Karel; Keller, Jiří; Jech, Robert; Dušek, Petr; Bezdicek, Ondrej; Krupička, Radim (Neurological sciences, 2024)
OBJECTIVE: To date, very few studies have focused on structural changes and their association with cognitive performance in isolated REM sleep behaviour disorder (iRBD). Moreover, the results of these studies are inconclusive. This study aims to evaluate differences in the associations between brain morphology and cognitive tests in iRBD and healthy controls. METHODS: Sixty-three patients with iRBD and thirty-six controls underwent MRI with a 3 T scanner. The cognitive performance was assessed by a comprehensive neuropsychological battery. Based on performance, the iRBD group was divided into two subgroups with (iRBD-MCI) and without mild cognitive impairment (iRBD-NC). The high-resolution T1-weighted images were analysed using an automated atlas segmentation tool, voxel-based (VBM) and deformation-based (DBM) morphometry to identify between-group differences and correlations with cognitive performance. RESULTS: VBM, DBM and the comparison of ROI volumes yielded no significant differences between iRBD and controls. In the iRBD group, significant correlations in VBM were found between several cortical and subcortical structures primarily located in the temporal, parietal, occipital lobe, cerebellum, and basal ganglia and three cognitive tests assessing psychomotor speed and one memory test. Between-group analysis of cognition revealed a significant difference between iRBD-MCI and iRBD-NC in tests including a processing speed component. CONCLUSIONS: iRBD shows deficits in several cognitive tests that correlate with morphological changes, the most prominent of which is in psychomotor speed and visual attention as measured by the TMT-A and associated with the volume of striatum, insula, cerebellum, temporal lobe, pallidum and amygdala.
Keywords: kognitivní dysfunkce; Cognition; Cerebellum; Mild cognitive impairment; porucha chování v REM spánku; kognice; Synucleinopathy; Trail Making Test; lidé; spánkový lalok; REM Sleep Behavior Disorder; Cognitive Dysfunction; Prodromal; Temporal Lobe; REM sleep without atonia; mozeček; Humans